Chemical and thermal impacts of sprite streamers in the Earth's mesosphere. Issue 10 (15th October 2015) - Parra‐Rojas, F. C.; Luque, A.; Gordillo‐Vázquez, F. J.
Abstract: A one‐dimensional self‐consistent model has been developed to study the chemical and thermal effects of a single sprite streamer in the Earth's mesosphere. We have used sprite streamer profiles with three different driving current durations (5 ms, 50 ms, and 100 ms) between 50 and 80 km of altitude and considering a kinetic scheme of air with more than 90 chemical species. Our model predicts strong increases in practically all the concentrations of the species studied at the moment of the streamer head passage. Moreover, their densities remain high during the streamer afterglow phase. The concentration of electrons can reach values of up to 10 8  cm −3 in the three cases analyzed. The model also predicts an important enhancement, of several orders of magnitude above ambient values, of nitrogen oxides and several metastables species. On the other hand, we found that the 4.26 μm IR emission brightness of CO2 can reach 10 GR at low altitudes (< 65 km) for the cases of intermediate (50 ms) and long (100 ms) driving currents. These results suggest the possibility of detecting sprite IR emissions from space with the appropriate instrumentation. Finally, we found that the thermal impact of sprites in the Earth's mesosphere is proportional to the driving current duration. This produces variations of more than 40 K (in the extreme case of a 100 ms driving current) at low altitudes (< 55 km) and at about 10 s after the streamer head. Key Points: Chemical and thermal impacts of sprites in the mesosphere are calculated The calculated concentration of electrons exhibits a significant enhancement The model predicts an increase in the gas temperature at low altitudes